Respiratory Distress Syndrome in Infants Delivered via Cesarean from Mothers with Preterm Premature Rupture of Membranes: A Propensity Score Analysis - Mariko Nakahara; Shunji Goto; Eiji Kato; Atsuo Itakura; Satoru Takeda (Journal of Pregnancy)
Objective. This study aimed to clarify the effects of cesarean delivery on neonatal respiratory morbidity when women had preterm premature rupture of membranes. Methods. This retrospective study included women with preterm premature rupture of membranes who delivered from 23 weeks to 33 weeks of gestation between January 2009 and December 2014. Neonatal outcomes were compared between infants delivered by cesarean section and those delivered vaginally. The primary outcome was respiratory distress syndrome (RDS). Neonatal intubation and mechanical ventilation periods were secondary outcomes. Propensity score matching was used to compare outcomes between cesarean and vaginal delivery cases. Results. There were 101 cesarean deliveries and 89 vaginal deliveries. A comparison of the presence or absence of neonatal complications based on the delivery type indicated a higher occurrence of RDS with cesarean deliveries (P=0.025). The intubation and mechanical ventilation periods were not significantly longer in neonates delivered via cesarean section. Conclusions. Cesarean delivery is a risk factor for neonatal RDS in women with preterm premature rupture of membranes. Trials identifying long-term neonatal prognoses are needed to further develop optimal management strategies in such cases.